Religious education for spiritual bricoleurs? the perceptions of students in ten Christian-ethos secondary schools in England and Wales - Casson, Ann (Journal of beliefs and values, 2020)
Religious Education (RE) in England and Wales functions within a post-secular culture. In the last fifty years, approaches characterised by academic rigour, impartiality, and professionalism have been prioritised. In this post-secular culture, the notion of bricolage aptly describes how some young people seek meaning, explore the spiritual dimension of life, with fragmented understandings of, experiences and encounters with the religious traditions. This paper draws on data from an empirical research project involving 350 students, to explore why students in ten Christian-ethos secondary schools in England and Wales recognised Religious Education (RE) as a significant contributor to their spiritual development. The analysis is illuminated by employing the concept of a narthical learning space (NLS) as the lens with which to examine young people's experiences. Three aspects of RE are explored: the debating of existential questions; opportunities to theologise and reflect; and encounters with the beliefs, practices, and opinions of others. This article argues that the concept of RE as a narthical learning space alongside the notion of young people as spiritual bricoleurs illuminates how the students in this study interpret the contribution of RE to their spiritual development.